Effects of increased student enrolments in a Bachelor of Nursing programme on health care service delivery - Daniels, F (South African Journal of Higher Education, 2016)
Nurse shortages in the Western Cape Region in South Africa led to increased student enrollments in the Bachelor of Nursing programme at the University of the Western Cape since 2004. A qualitative, exploratory, descriptive study was conducted between 2010 and 2012 to determine the effects of the increased nursing student enrollment on the health care service delivery in the Western Cape. Nine (9) nurse managers from public health facilities in the region participated in in-depth individual interviews and one focus group discussion was conducted with six (6) clinical supervisors who accompanying the students in the clinical facilities. The study found both direct and indirect adverse effects on service delivery. The changing learning environment, competition for learning opportunities and limitations posed challenges on professional nurses to perform their multifaceted role which includes clinical teaching and mentoring affected service delivery. Therefore, careful planning of students’ learning experiences in both theory and practices is imperative to ensure that teaching and learning and service delivery is not negatively affected.